Life of Fred. Ducks / Book 5 - Schmidt, Stanley F. (Stanley Fredric), 1944- (Reno, Nev. : Polka Dot Publishing, 2015)
This delightful romp for young beginning readers unfolds over the 18 books of the series as Fred (age 4) and Kingie (his doll) go on an exciting adventure. These storybooks also teach colors, shapes, the word "STOP," and how to make mashed potatoes.
Set 1 (6 New Hardback Readers). Life of Fred Eden Series containing the titles: Blue, Bus, Lake, Potato Dreams, Ducks, and Rain.
"book #5"--Cover.
"Life of Fred for the beginning reader: pink"--Back cover.
Set 1 (book #1-6)- JBR1 ; Set 2 (book #7-12)- JBR2 ; Set 3 (book #13-18)- JBR3.
JBR1 mc (JBRNF as requested by ANS) (Levels will be assigned) mc
Keywords: Pink -- Juvenile literature; Colors -- Juvenile literature; Ducks -- Juvenile literature; Reading (Early childhood) -- Juvenile literature; Reading readiness -- Juvenile literature; Home schooling -- United States -- Juvenile literature; Readers (Primary) -- Juvenile literature; Beginning readers book